The Impact of Supply Chain Management Practices on the Operational Performance of 5-star Hotels Operating in Jordan - Almufleh, Nawaf Ma’moun; Alkhatib, Saleh Fahed (Jordan Journal of Business Administration, 2023)
This study aims to identify the impact of supply chain management practices on the operational performance of five-star hotels operating in Jordan. A special questionnaire was designed and distributed to marketing, procurement and inventory managers. The results show that the level of supply chain management practices (customer relations, supplier relations and internal processes) and the level of operational performance (flexibility, quality and time) were generally high, with a statistically significant positive relationship between these practices and operational performance in all dimensions, except for relations with suppliers and time. Furthermore, there were no statistically significant differences in the hotels’ responses due to age and spread degree.